Fe-element-free layered oxide positive electrode material, preparation method thereof, positive electrode composition, sodium ion secondary battery and application
By regulating the composition of the Fe-free layered oxide positive electrode material, the initial discharge specific capacity, magnification and cycling performance of sodium ion secondary batteries are improved, and the safety performance is improved, and the shortcomings in energy density and safety of existing materials are solved. .
Patent Information
- Application Number
- CN202411320640.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
AI Technical Summary
The layered oxide cathode materials of existing sodium ion secondary batteries have shortcomings in energy density, rate performance, cycle performance and safety performance, and are difficult to meet the market's demand for high-performance materials.
Develop a layered oxide cathode material without Fe element, with the general formula of Na2y+2sCuxNiyMn1-yTijHs-xO2+2s+2j, and regulates Cu, Ti, Ni, Mn, Zn, Mg, Ca, Sr, and Ba The content, as well as the content relationship between +2-valent doping elements and Cu and Ti, improves the initial discharge specific capacity, rate performance and cycling performance, and improves safety performance.
Achieve high initial discharge specific capacity (such as greater than 165mAh/g), improved rate performance (0.5C/0.1C ratio greater than 0.90) and cycle performance (100 cycle capacity retention rate greater than 0.90 at 0.5C ratio), and better The safety performance and delayed peak position indicate that the high temperature resistance is better than that of Fe-containing materials.
Smart Images

Figure CN119153681A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of energy storage technology, in particular to the field of sodium ion secondary batteries. Specifically, the present invention relates to a layered oxide positive electrode material without Fe element, a preparation method thereof, a positive electrode composition comprising the layered oxide positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and uses of the sodium ion secondary battery. Background Art
[0002] Sodium-ion secondary batteries have a similar structural principle to lithium-ion secondary batteries, and work by repeatedly embedding, transferring, and transmitting sodium ions between the positive and negative electrodes. Compared with lithium-ion secondary batteries, sodium-ion secondary batteries have the advantages of abundant resources and low raw material costs, which are conducive to achieving cheap large-scale energy storage and large-scale commercial applications, and have been developed very rapidly in recent years.
[0003] The current industrialized sodium ion cathode materials are represented by layered oxides. One of the core issues facing sodium ion layered oxide cathode materials is how to effectively improve energy density. In addition, with the increasing popularity of electronic products in people's daily lives, people's requirements for the rate performance, cycle performance, safety performance, etc. of sodium ion secondary batteries are also getting higher and higher.
[0004] Therefore, the art still needs to develop a new layered oxide positive electrode material with higher initial discharge specific capacity (gram capacity), rate performance and cycle performance, as well as good safety performance, so as to better meet market demand. Summary of the invention
[0005] The present invention is made in view of the above problems existing in the prior art.
[0006] In a first aspect, the present invention relates to a Fe-free layered oxide positive electrode material having the following general formula:
[0007] Na 2y+2s Cu x Ni y Mn 1-y Ti j H s-x O 2+2s+2j
[0008] Among them, 0.03≤x≤0.11, preferably 0.03≤x≤0.08; 0.40≤y≤0.50, preferably 0.45≤y≤0.50, more preferably 0.47≤y≤0.50; 0.08≤j≤0.16, preferably 0.08≤j≤0.14, for example 0.08≤j≤0.12 or 0.12≤j≤0.14; x+0.04<s≤j+0.02; H is a +2 valence active metal element, and H includes the following The invention relates to a Zn content of more than 0.020, preferably in the range of 0.020 to 0.040, more preferably in the range of 0.020 to 0.030, and a Mg content of more than 0.020, preferably in the range of 0.020 to 0.050, more preferably in the range of 0.020 to 0.030, and further comprises one or more of Ca, Sr and Ba, wherein each of the subscripts of Ca, Sr and Ba when present is less than or equal to 0.010; the general formula satisfies the valence balance.
[0009] In a second aspect, the present invention relates to a method for preparing the layered oxide positive electrode material according to the first aspect of the present invention, comprising the following steps:
[0010] Step a: uniformly mixing a Na source, a Cu source, a Ti source, a Ni source, a Mn source, and a H source in a stoichiometric ratio, wherein the H source comprises a Zn source, a Mg source, and further comprises one or more of a Ca source, a Sr source, and a Ba source; and
[0011] Step b: sintering the mixture obtained in step a at 800 to 1000° C. for 10 to 30 hours, cooling, and optionally crushing and sieving.
[0012] In a third aspect, the present invention relates to a positive electrode composition, which comprises the Fe-free layered oxide positive electrode material according to the first aspect of the present invention.
[0013] In a fourth aspect, the present invention relates to a sodium ion secondary battery, comprising the positive electrode composition according to the third aspect of the present invention.
[0014] In a fifth aspect, the present invention relates to the use of the sodium ion secondary battery of the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0015] The inventor unexpectedly discovered in the study that by regulating the composition of the Fe-free layered oxide positive electrode material, including the content of Cu, Ti, Ni, Mn, and doping elements Zn, Mg, and optional Ca, Sr, Ba, and the content relationship between the +2-valent doping element and Cu and Ti, the initial discharge specific capacity of the Fe-free layered oxide positive electrode material can be increased, and the rate performance and cycle performance can be improved. In addition, the inventor also found that compared with the Fe-containing layered oxide positive electrode material, the Fe-free layered oxide positive electrode material of the present invention has better safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the present invention, the following will briefly describe the drawings required for describing the embodiments. It should be understood that these drawings are only for the convenience of technicians to understand the present invention more easily, and are not intended to limit the scope of the present invention.
[0017] Figure 1 This is a first charge and discharge curve diagram of a button cell prepared using the positive electrode active material prepared according to Example 1 of the present invention;
[0018] Figure 2 This is a first charge and discharge curve diagram of a button cell prepared using the positive electrode active material prepared according to Example 2 of the present invention;
[0019] Figure 3 This is a graph showing the first charge and discharge curve of a button cell prepared using the positive electrode active material prepared according to Example 3 of the present invention;
[0020] Figure 4 This is a first charge and discharge curve diagram of a button cell prepared using the positive electrode active material prepared according to Example 4 of the present invention;
[0021] Figure 5 This is a first charge and discharge curve diagram of a button cell prepared using the positive electrode active material prepared according to Example 5 of the present invention;
[0022] Figure 6 This is a graph showing the first charge and discharge curve of a button cell prepared using the positive electrode active material prepared according to Example 6 of the present invention;
[0023] Figure 7 The first charge and discharge curve of a button cell prepared using the positive electrode active material prepared in Comparative Example 5 of the present invention;
[0024] Figure 8 The XRD (X-ray diffraction) spectrum of the layered oxide positive electrode material according to Example 1 of the present invention and the standard XRD spectrum PDF#54-0887 (O3) are shown;
[0025] Fig. 9This is a SEM (scanning electron microscope)-EDS (X-ray energy dispersive spectrometer) picture of the layered oxide positive electrode material according to Example 1 of the present invention;
[0026] Fig.10 This is a SEM picture of the layered oxide positive electrode material according to Comparative Example 5 of the present invention;
[0027] Fig.11 This is a SEM picture of the layered oxide positive electrode material according to Example 2 of the present invention;
[0028] Fig.12 is a SEM picture of the layered oxide positive electrode material according to Example 3 of the present invention; and
[0029] Fig.13 1 and 2 are DSC (Differential Scanning Calorimetry) spectra of the layered oxide positive electrode materials according to Example 6 and Comparative Example 15 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0031] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0032] The present invention relates to a layered oxide positive electrode material without Fe element, a preparation method thereof, a positive electrode composition comprising the layered oxide positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and use of the sodium ion secondary battery.
[0033] The present invention will be described in detail below.
[0034] Fe-free layered oxide cathode materials
[0035] In a first aspect, the present invention relates to a Fe-free layered oxide positive electrode material having the following general formula:
[0036] Na 2y+2s Cu x Ni y Mn 1-y Ti j H s-x O 2+2s+2j
[0037] Among them, 0.03≤x≤0.11, preferably 0.03≤x≤0.08; 0.40≤y≤0.50, preferably 0.45≤y≤0.50, more preferably 0.47≤y≤0.50; 0.08≤j≤0.16, preferably 0.08≤j≤0.14, for example 0.08≤j≤0.12 or 0.12≤j≤0.14; x+0.04<s≤j+0.02; H is a +2 valence active metal element, and H includes the following The invention relates to a Zn content of more than 0.020, preferably in the range of 0.020 to 0.040, more preferably in the range of 0.020 to 0.030, and a Mg content of more than 0.020, preferably in the range of 0.020 to 0.050, more preferably in the range of 0.020 to 0.030, and further comprises one or more of Ca, Sr and Ba, wherein each of the subscripts of Ca, Sr and Ba when present is less than or equal to 0.010; the general formula satisfies the valence balance.
[0038] The inventor unexpectedly found in the study that by regulating the composition of the Fe-free layered oxide positive electrode material, including the content of Cu, Ti, Ni, Mn and doping elements Zn, Mg and optional Ca, Sr, Ba, and the content relationship of the +2-valent doping element with Cu and Ti, the initial discharge specific capacity of the Fe-free layered oxide positive electrode material can be increased, and the rate performance and cycle performance can be improved. The Fe-free layered oxide positive electrode material of the present invention has excellent initial discharge gram capacity (for example, greater than 165 mAh / g, for example, greater than 170 mAh / g, for example, greater than 180 mAh / g (for example, at 0.1C)), and improved rate performance (for example, the ratio of the initial discharge specific capacity at a rate of 0.5C to the initial discharge specific capacity at a rate of 0.1C (hereinafter referred to as 0.5C / 0.1C) is greater than 0.90, for example, greater than 0.95) and cycle performance (the cycle capacity retention rate after 100 cycles at a rate of 0.5C is greater than 0.90, for example, greater than 0.92). In addition, the inventors have also found that the Fe-free layered oxide positive electrode material of the present invention has better safety performance than the layered oxide positive electrode material containing the Fe element. For example, compared with the layered oxide positive electrode material containing the Fe element, the peak position of the Fe-free layered oxide positive electrode material of the present invention is further back, which indicates that it can withstand higher temperatures and has better safety performance.
[0039] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the range of the subscript x of Cu is 0.03≤x≤0.11, preferably 0.03≤x≤0.08. For example, the subscript x of Cu is 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, or within the range defined by any two of them. The inventors found in the study that for the layered oxide positive electrode material system of the present invention, compared to the case where the subscript of Cu is not within the above range, when the subscript of Cu is within the above range, an increased initial discharge specific capacity, as well as improved rate performance and cycle performance can be obtained. Further, when the subscript of Cu is in the range of 0.03-0.08, the improvement in initial discharge specific capacity is more obvious.
[0040] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the range of the subscript y of Ni is 0.40≤y≤0.50, preferably 0.45≤y≤0.50, and more preferably 0.47≤y≤0.50. For example, the subscript y of Ni is 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, or within the range defined by any two of them. Compared to the case where the subscript of Ni is not within the above range, when the subscript of Ni is within the above range, an increased initial discharge specific capacity, as well as improved rate performance and cycle performance can be obtained. Further, when the subscript of Ni is in the range of 0.45-0.50, more preferably 0.47-0.50, the improvement in initial discharge specific capacity is more obvious.
[0041] In some embodiments, in the general formula of the layered oxide positive electrode material without Fe element of the present invention, the subscript of Mn element is 1-y. For example, the subscript of Mn element is in the range of 0.50 to 0.60, preferably 0.50 to 0.55, more preferably 0.50 to 0.53. For example, the subscript of Mn element is 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, or in the range defined by any two of them. Compared with the case where the subscript of Mn is not in the above range, when the content of Mn is in the above range, the improvement in initial discharge specific capacity is more obvious.
[0042] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the range of the subscript j of the Ti element is 0.08≤j≤0.16, preferably 0.08≤j≤0.14, for example 0.08≤j≤0.12 or 0.12≤j≤0.14. For example, the subscript j of the Ti element is 0.080, 0.090, 0.100, 0.110, 0.120, 0.130, 0.140, 0.150, 0.160, or within the range defined by any two of them. Compared to the case where the subscript of Ti is not within the above range, when the subscript of Ti is within the above range, an increased initial discharge specific capacity, as well as improved rate performance and cycle performance can be obtained. Further, when the subscript of Ti is in the range of 0.08-0.14, the improvement in initial discharge specific capacity is more obvious.
[0043] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, s and j satisfy: x+0.04<s≤j+0.02. After summarizing and analyzing a large number of experiments, the inventors found that when x, s and j satisfy the above relationship, an improved initial discharge specific capacity and / or rate performance can be obtained compared to the case where the above relationship is not satisfied.
[0044] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, s is in the range of 0.10 to 0.18, preferably 0.10 to 0.13. For example, s may be 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, or in the range defined by any two of them. When s is within the above range, it helps to further improve the initial discharge specific capacity.
[0045] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the doping element H includes Zn with a subscript of more than 0.020, preferably in the range of 0.020 to 0.040, more preferably in the range of 0.020 to 0.030, and Mg with a content of more than 0.020, preferably in the range of 0.020 to 0.050, more preferably in the range of 0.020 to 0.030. For example, the subscript of Zn may be 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, 0.100, or any two of them within the range defined, and the subscript of Mg may be 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, 0.100, 0.110, 0.120, 0.130, 0.140, 0.150, or any two of them within the range defined. After conducting a large number of studies, the inventors found that compared to the case where the subscript of Zn is lower than the above range, when the subscript of Zn is within the above range, an increased initial discharge specific capacity, as well as improved rate performance and cycle performance can be obtained. Further, when the subscript of Zn is in the range of 0.020-0.040, more preferably 0.020-0.030, it is beneficial to further improve the initial discharge specific capacity. Similarly, compared with the case where the subscript of Mg is lower than the above range, when the subscript of Mg is in the above range, an increased initial discharge specific capacity, as well as improved rate performance and cycle performance can be obtained. Further, when the subscript of Mg is in the range of 0.020-0.050, more preferably 0.020-0.030, it is beneficial to further improve the initial discharge specific capacity.
[0046] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the doping element H further comprises one or more of Ca, Sr, and Ba, each with a subscript of ≤0.010. In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material, the sum of the subscripts of Ca, Sr, and Ba is 0.001 to 0.010, for example, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or within the range defined by any two of them. As an example, the doping element H may further include Ca with a subscript in the following range: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or a range defined by any two of them; or the doping element H may further include Sr with a subscript in the following range: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or within the range defined by any two of them; or the doping element H may further include Ba with subscripts in the following ranges: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or within the range defined by any two of them; or the doping element H may further include Ca and Sr with subscripts in the following ranges: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or the range defined by any two of them; or the doping element H may further include Ca and Ba with respective subscripts in the following ranges: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or the range defined by any two of them; or the doping element H may further include Sr and Ba with respective subscripts in the following ranges: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or the range defined by any two of them; 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or the range defined by any two of them; or the doping element H may further include Ca, Sr and Ba with respective subscripts in the following ranges: 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, or the range defined by any two of them.
[0047] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the doping element H is one selected from Zn+Mg+Ca, Zn+Mg+Sr, Zn+Mg+Ba, Zn+Mg+Ca+Sr, Zn+Mg+Ca+Ba, Zn+Mg+Sr+Ba, and Zn+Mg+Ca+Sr+Ba.
[0048] In addition, the inventors have found through research that when the Fe-free layered oxide positive electrode material of the present invention meets one or more of the following conditions, it helps to further improve the initial discharge specific capacity and improve the rate performance and cycle performance.
[0049] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the subscript 2y+2s of the Na element is in the range of 1.00 to 1.40, preferably 1.10 to 1.30. For example, the subscript of the Na element can be 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.40, or within the range defined by any two of them.
[0050] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the (total) subscript of the doping element H (i.e., sx) is in the range of 0.040 to 0.080, preferably 0.045 to 0.070, and more preferably 0.050 to 0.070. For example, the total subscript of the doping element H may be 0.040, 0.041, 0.042, 0.043, 0.044, 0.045, 0.046, 0.047, 0.048, 0.049, 0.050, 0.051, 0.052, 0.053, 0.054, 0.055, 0.056, 0.057, 0.058, 0.059, 0.06 0.061, 0.062, 0.063, 0.064, 0.065, 0.066, 0.067, 0.068, 0.069, 0.070, 0.071, 0.072, 0.073, 0.074, 0.075, 0.076, 0.077, 0.078, 0.079, 0.080, or the range defined by any two of them.
[0051] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the subscript 2+2s+2j of the O element is in the range of 2.20 to 2.80. For example, the subscript of the O element may be 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, or within the range defined by any two of them. It is easy for a person skilled in the art to understand that the general formula of the Fe-free layered oxide positive electrode material satisfies the valence balance. In the general formula of the layered oxide positive electrode material of the present invention, the amount of various elements other than O and the relative proportion relationship are determined, but the amount of O may have a certain error due to the presence of air or an oxidizing atmosphere, for example, the amount of the O element or the error of the subscript may be in the range of ±10% or ±5%, and the general formula of the layered oxide positive electrode material satisfies the valence balance as a whole.
[0052] In some embodiments, in the general formula of the Fe-free layered oxide positive electrode material of the present invention, the molar ratio of Cu to Ni is in the range of 0.06 to 0.28, preferably 0.06 to 0.18, for example 0.06 to 0.16. For example, the molar ratio of Cu to Ni may be 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, or in the range defined by any two of them.
[0053] In some embodiments, the Fe-free layered oxide cathode material of the present invention is an O3 phase cathode material. The phase of the layered oxide cathode material can be determined by analyzing the XRD spectrum of the layered oxide cathode material.
[0054] Preparation method of Fe-free layered oxide positive electrode material
[0055] The second aspect of the present invention provides a method for preparing a layered oxide positive electrode material without Fe element according to the first aspect of the present invention, which comprises the following steps:
[0056] Step a: uniformly mixing a Na source, a Cu source, a Ti source, a Ni source, a Mn source, and a H source in a stoichiometric ratio, wherein the H source comprises a Zn source, a Mg source, and further comprises one or more of a Ca source, a Sr source, and a Ba source; and
[0057] Step b: sintering the mixture obtained in step a at 800 to 1000° C. for 10 to 30 hours, cooling, and optionally crushing and sieving.
[0058] Step a
[0059] In step a, a Na source, a Cu source, a Ti source, a Ni source, a Mn source, and a H source are uniformly mixed in a stoichiometric ratio, and the H source comprises a Zn source, a Mg source, and further comprises one or more of a Ca source, a Sr source, and a Ba source.
[0060] In some embodiments, the Na source, Cu source, Ti source, Ni source, Mn source, and H source may be any compound containing Na, Cu, Ti, Ni, Mn, and doping element H known to those skilled in the art for preparing positive electrode materials for sodium ion secondary batteries. For example, in step a, the Na source, Cu source, Ti source, Ni source, Mn source, Zn source, Mg source, Ca source, Sr source, and Ba source may be selected from one or more of carbonates, bicarbonates, nitrates, acetates, oxalates, hydroxides, and oxides of the corresponding elements, respectively. As an example, the Na source is one or more selected from the following compounds: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide and sodium oxide; the Cu source is one or more selected from the following compounds: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide, copper oxide and cuprous oxide; the Ti source is one or more selected from the following compounds: titanium carbonate, titanium nitrate, titanium acetate, titanium oxalate, titanium hydroxide and titanium oxide; the Ni source is one or more selected from the following compounds: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel manganese hydroxide and nickel oxide; the Mn source is one or more selected from the following compounds: manganese carbonate, manganese nitrate, manganese acetate, manganese oxalate, manganese hydroxide, manganese oxide manganese dioxide, nickel manganese hydroxide and manganese oxide; the Zn source is one or more selected from the following compounds: zinc carbonate, zinc nitrate, zinc acetate, zinc oxalate, zinc hydroxide and zinc oxide; the Mg source is one or more selected from the following compounds: magnesium carbonate, magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide and magnesium oxide; the Ca source is one or more selected from the following compounds: calcium carbonate, calcium nitrate, calcium acetate, calcium oxalate, calcium hydroxide and calcium oxide; the Sr source is one or more selected from the following compounds: strontium carbonate, strontium nitrate, strontium acetate, strontium oxalate, strontium hydroxide and strontium oxide; and the Ba source is one or more selected from the following compounds: barium carbonate, barium nitrate, barium acetate, barium oxalate, barium hydroxide and barium oxide.
[0061] Step b
[0062] In step b, the mixture obtained in step a is sintered at 800 to 1000° C. for 10 to 30 hours, cooled, and optionally crushed and sieved.
[0063] In step b, the sintering temperature is in the range of 800 to 1000° C. For example, the sintering temperature is 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000° C., or in the range defined by any two of them.
[0064] In step b, the sintering time is in the range of 10 to 30 hours. For example, the sintering time can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 hours, or any two thereof.
[0065] In step b, the heating rate for sintering is not particularly limited and can be 1-10°C / min, preferably 2-5°C / min, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10°C / min, or within the range defined by any two of them.
[0066] The sintering may be carried out in an oxidizing atmosphere. Preferably, the oxidizing atmosphere is compressed air or oxygen. The pressure of the compressed air may be any commonly used pressure, such as 0.10 MPa or more, such as 0.20-0.40 MPa. The pressure of the oxidizing atmosphere is 0.10 MPa or more, such as 0.15 MPa-0.35 MPa.
[0067] In the method of the present invention, the cooling, crushing and screening in step b can be performed by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling or water cooling. For example, the crushing can be air flow crushing or mechanical crushing.
[0068] In some embodiments, after pulverization, the D of the layered oxide positive electrode material is v 50 The particle size is in the range of 2.0-20.0 μm, for example, 5.0-15.0 μm. In this context, D v The 50 particle size refers to the particle size smaller than this particle size value and the particle size larger than this particle size value in the volume cumulative distribution curve of the layered oxide positive electrode material, each accounting for 50% of the total sample volume. v The particle size can be measured by methods commonly used in the art. For example, a Malvern 3000 laser particle size analyzer can be used for testing. As an example, the D of the layered oxide positive electrode material vThe particle size may be 2.0, 3.0, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0 μm, or within the range defined by any two of them.
[0069] In some embodiments, the present invention also relates to a Fe-free layered oxide positive electrode material prepared by the method of the present invention.
[0070] Positive electrode composition
[0071] A third aspect of the present invention provides a positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the Fe-free layered oxide positive electrode material according to the first aspect of the present invention.
[0072] In addition to the Fe-free layered oxide positive electrode material of the present invention, the positive electrode composition (for sodium ion secondary battery) may also include a conductive agent, a binder and any other substances that can be used by those skilled in the art as needed, such as a dispersant and an additive for improving stability.
[0073] In some embodiments, based on the dry weight of the positive electrode composition (for sodium ion secondary battery), the content of the Fe-free layered oxide positive electrode material may be a common amount in the art, for example, 70-95 wt %, for example 80-90 wt %.
[0074] The type of conductive agent is not particularly limited, as long as it has the performance of enhancing the positive electrode conductivity and not adversely affecting the layered oxide positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As an example, the conductive agent used for the positive electrode composition (for sodium ion secondary battery) can be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0075] In some embodiments, based on the dry weight of the positive electrode composition (for sodium ion secondary battery), the content of the conductive agent may be a common amount in the art, such as 1-10 wt %, such as 2-5 wt %.
[0076] The binder is not particularly limited as long as it has the properties of enhancing the adhesion between the positive electrode active material particles and the adhesion to the current collector and does not adversely affect the performance of the layered oxide positive electrode material. Those skilled in the art can select according to actual needs. As an example, the binder for the positive electrode composition for the sodium ion secondary battery can be selected from polyfluoroolefin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives and styrene-butadiene rubber, acrylic resin, carboxymethyl cellulose, polyvinyl alcohol (PVA), etc. One or more.
[0077] In some embodiments, based on the dry weight of the positive electrode composition (for a sodium ion secondary battery), the content of the binder is 1-10 wt %, for example, 2-5 wt %.
[0078] The positive electrode composition may be in the form of a slurry, that is, it may further include a solvent. The positive electrode composition may also be in a dry form, that is, it does not include a solvent, for example, it may be in the form of a positive electrode active material layer disposed on a positive electrode current collector.
[0079] Sodium ion secondary battery
[0080] A fourth aspect of the present invention provides a sodium ion secondary battery. A sodium ion secondary battery generally includes a positive electrode, a negative electrode, a separator and an electrolyte.
[0081] In some embodiments, the sodium ion secondary battery may further include an outer package for encapsulating the electrode assembly and the electrolyte. For example, the outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or a soft package, such as a bag-type soft package, such as a soft package made of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0082] The shape of the sodium ion secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.
[0083] The sodium ion secondary battery can be prepared by a method commonly used in the art. For example, the positive electrode sheet, the negative electrode sheet and the separator can be made into a battery cell through a winding process or a lamination process, and then the electrolyte is injected.
[0084] positive electrode
[0085] The positive electrode (or positive electrode sheet) comprises a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising the positive electrode composition of the third aspect of the present invention, for example in dry form. The positive electrode also forms an aspect of the present invention.
[0086] The positive electrode current collector is not particularly limited, and the positive electrode current collector commonly used by those skilled in the art may be used. As an example, the positive electrode current collector may be a metal foil such as aluminum foil, nickel foil, or a composite current collector. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), 1,3-propane sultone (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0087] The positive electrode sheet can be prepared according to the method commonly used in the art.
[0088] For example, the positive electrode can be formed by uniformly dispersing a positive electrode active material, a conductive agent, and a binder in a solvent (eg, N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; coating the slurry on a positive electrode current collector, drying, and pressing.
[0089] Alternatively, the positive electrode can also be formed by uniformly dispersing the positive electrode active material, the conductive agent, and the binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; casting the positive electrode slurry on a separate carrier, drying, separating the obtained positive electrode film from the carrier and laminating it on a positive electrode current collector.
[0090] negative electrode
[0091] The negative electrode (or negative electrode plate) may be a metal sodium plate, or may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0092] The negative electrode current collector is not particularly limited, and the negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil such as copper foil, or a composite current collector. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0093] In some embodiments, the negative electrode active material may be an active material commonly used by those skilled in the art. For example, the negative electrode active material may be one or more of natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon-based materials, tin-based materials, lithium titanate, and metallic sodium. Among them, the silicon-based material may be one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys, and the tin-based material may be one or more of elemental tin, tin oxide compounds, and tin alloys.
[0094] In some embodiments, the negative electrode active material may be contained in an amount of 70-95 wt %, for example 80-90 wt %, based on the total weight (dry weight) of the negative electrode active material layer.
[0095] In addition to the negative electrode active material, the negative electrode active material layer may further include a binder, a conductive agent and any other optional auxiliary agents such as a thickener.
[0096] There is no particular requirement for the negative electrode conductive agent. As an example, the conductive agent can be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0097] In some embodiments, the conductive agent may be present in an amount of 1-10 wt %, for example 2-5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.
[0098] There is no special requirement for the negative electrode binder. As an example, the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC).
[0099] In some embodiments, the content of the binder may be 1-10 wt %, for example 2-5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.
[0100] The negative electrode can be prepared according to a method commonly used in the art.
[0101] For example, the negative electrode can be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (such as N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode current collector, drying, and pressing.
[0102] Alternatively, the negative electrode can also be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (e.g., N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; casting the negative electrode slurry on a separate carrier, drying, separating the obtained negative electrode film from the carrier and laminating it on a negative electrode current collector.
[0103] Electrolytes
[0104] The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte is not particularly limited and can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).
[0105] In some embodiments, the electrolyte is an electrolyte solution, which includes an organic aprotic solvent and an electrolyte sodium salt.
[0106] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0107] In some embodiments, the electrolyte sodium salt can be selected from one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroborate (NaBF6), sodium bis(trifluoromethylsulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium trifluoromethylsulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0108] In some embodiments, the concentration of sodium ions in the electrolyte is 0.2-2 mol / L, such as 0.5-1.0 mol / L.
[0109] In some embodiments, the electrolyte may further include additives, for example, additives that help negative electrode film formation or positive electrode film formation, and additives that can improve battery performance, such as additives that improve high or low temperature performance of the battery.
[0110] Diaphragm
[0111] The separator is not particularly limited, and a commonly used porous structure separator with electrochemical stability and chemical stability can be used, for example, it can be a single layer or multilayer film of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. When a solid electrolyte is used, the separator can also be omitted.
[0112] use
[0113] The fifth aspect of the present invention provides the use of the sodium ion secondary battery according to the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0114] Those skilled in the art will appreciate that the sodium ion secondary battery of the fourth aspect of the present invention may also be used for other purposes. For example, the sodium ion secondary battery may be used as a power source or energy storage unit in a mobile device (e.g., a mobile phone, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, an electric bicycle, an electric scooter, etc.), an electric train, etc.
[0115] Example
[0116] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0117] 1. Preparation Example
[0118] Example 1
[0119] The general formula for preparation is Na 1.150 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Zn 0.020 Mg 0.020 Ca 0.005 O 2.530 Layered oxide cathode materials:
[0120] Sodium carbonate, cuprous oxide, and nickel manganese hydroxide (Ni / Mn molar ratio is 0.45 / 0.55, i.e., Ni 0.45 Mn0.55 (OH)2, the same as the Ni / Mn ratio in the layered oxide positive electrode material, the same below), titanium dioxide, zinc oxide, magnesium carbonate and calcium oxide are mixed uniformly to obtain a mixture. The obtained mixture is then sintered at 900°C in an air atmosphere for 20 hours, and then cooled (naturally cooled to room temperature in the sintering atmosphere, the same below), and crushed (air flow crushing, feeding frequency 10Hz, air flow pressure 0.5Mpa, classification frequency 80Hz, induced draft frequency 50Hz, the same below) to obtain a general formula of Na 1.150 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Zn 0.020 Mg 0.020 Ca 0.005 O 2.530 The layered oxide positive electrode material has a volume average particle size D v 50 is 8.5 microns.
[0121] Example 2
[0122] The general formula for preparation is Na 1.200 Cu 0.03 Ni 0.50 Mn 0.50 Ti 0.08 Zn 0.030 Mg 0.030 Sr 0.005 Ba 0.005 O 2.360 Layered oxide cathode materials:
[0123] Sodium bicarbonate, copper hydroxide, nickelous oxide (nickel oxide), manganese tetraoxide, titanium dioxide, zinc oxide, magnesium hydroxide, strontium carbonate and barium carbonate were weighed and mixed according to the stoichiometric ratio of the elements to obtain a mixture. The mixture was then sintered at 900°C in an air atmosphere for 20 hours, then cooled and crushed to obtain a general formula of Na 1.200 Cu 0.03 Ni 0.50 Mn 0.50 Ti 0.08 Zn 0.030 Mg 0.030 Sr 0.005 Ba 0.005 O 2.360 The layered oxide positive electrode material has a volume average particle size D v 50 is 7.5 microns.
[0124] Example 3
[0125] The general formula for preparation is Na 1.122 Cu 0.11 Ni0.40 Mn 0.60 Ti 0.16 Zn 0.030 Mg 0.020 Sr 0.001 O 2.642 Layered oxide cathode materials:
[0126] Sodium carbonate, copper oxide, nickelous oxide, manganese tetraoxide, titanium dioxide, zinc oxide, magnesium oxide and strontium carbonate were weighed and mixed according to the stoichiometric ratio of the elements to obtain a mixture. The mixture was then sintered at 900°C in an air atmosphere for 20 hours, and then cooled and crushed to obtain a general formula of Na 1.122 Cu 0.11 Ni 0.40 Mn 0.60 Ti 0.16 Zn 0.030 Mg 0.020 Sr 0.001 O 2.642 The layered oxide positive electrode material has a volume average particle size D v 50 is 9.5 microns.
[0127] Example 4
[0128] The general formula for preparation is Na 1.162 Cu 0.05 Ni 0.47 Mn 0.53 Ti 0.10 Zn 0.030 Mg 0.030 Sr 0.001 O 2.422 Layered oxide cathode materials:
[0129] Sodium carbonate, copper oxide, nickelous oxide, manganese tetraoxide, titanium dioxide, zinc oxide, magnesium oxide and strontium carbonate were weighed and mixed according to the stoichiometric ratio of the elements to obtain a mixture. The mixture was then sintered at 800°C in an air atmosphere for 30 hours, and then cooled and crushed to obtain a general formula of Na 1.162 Cu 0.05 Ni 0.47 Mn 0.53 Ti 0.10 Zn 0.030 Mg 0.030 Sr 0.001 O 2.422 The layered oxide positive electrode material has a volume average particle size D v 50 is 7.8 microns.
[0130] Example 5
[0131] The general formula for preparation is Na 1.130 Cu0.04 Ni 0.45 Mn 0.55 Ti 0.12 Zn 0.020 Mg 0.050 Ca 0.005 O 2.470 Layered oxide cathode materials:
[0132] Sodium carbonate, copper oxide, nickelous oxide, manganese tetraoxide, titanium dioxide, zinc oxide, magnesium oxide and calcium carbonate were weighed according to the stoichiometric ratio of the elements and mixed to obtain a mixture. The obtained mixture was then sintered at 1000°C in an air atmosphere for 10 hours, and then cooled and crushed to obtain a general formula of Na 1.130 Cu 0.04 Ni 0.45 Mn 0.55 Ti 0.12 Zn 0.020 Mg 0.050 Ca 0.005 O 2.470 The layered oxide positive electrode material has a volume average particle size D v 50 is 10.7 microns.
[0133] Example 6
[0134] The general formula for preparation is Na 1.260 Cu 0.08 Ni 0.50 Mn 0.50 Ti 0.12 Zn 0.020 Mg 0.020 Ca 0.006 Sr 0.002 Ba 0.002 O 2.500 Layered oxide cathode materials:
[0135] Sodium carbonate, copper oxide, nickelous oxide, manganese tetraoxide, titanium dioxide, zinc oxide, magnesium oxide, calcium oxide, strontium carbonate and barium carbonate were weighed according to the stoichiometric ratio of the elements and mixed to obtain a mixture. The obtained mixture was then sintered at 800°C in an air atmosphere for 30 hours, and crushed to obtain a general formula of Na 1.260 Cu 0.08 Ni 0.50 Mn 0.50 Ti 0.12 Zn 0.020 Mg 0.020 Ca 0.006 Sr 0.002 Ba 0.002 O 2.500 The layered oxide positive electrode material has a volume average particle size D v50 is 6.5 microns.
[0136] Comparative Example 1
[0137] The general formula for preparation is Na 1.146 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Zn 0.018 Mg 0.020 Ca 0.005 O 2.526 Layered oxide cathode materials:
[0138] The same procedures as in Example 1 were performed except that the Zn content was adjusted to 0.018. The volume average particle size D of the obtained layered oxide positive electrode material was v 50 is 8.5 microns.
[0139] Comparative Example 2
[0140] The general formula for preparation is Na 1.146 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Zn 0.020 Mg 0.018 Ca 0.005 O 2.526 Layered oxide cathode materials:
[0141] The other aspects were the same as in Example 1 except that the content of Mg was adjusted to 0.018. The volume average particle size D of the obtained layered oxide positive electrode material was v 50 is 8.5 microns.
[0142] Comparative Example 3
[0143] The general formula for preparation is Na 1.150 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Zn 0.040 Ca 0.005 O 2.530 Layered oxide cathode materials:
[0144] The same method as in Example 1 was used except that the Mg content of 0.020 and the Zn content of 0.020 were adjusted to 0.040. The volume average particle size D of the obtained layered oxide positive electrode material was v 50 is 8.5 microns.
[0145] Comparative Example 4
[0146] The general formula for preparation is Na 1.150 Cu0.08 Ni 0.45 Mn 0.55 Ti 0.14 Mg 0.040 Ca 0.005 O 2.530 Layered oxide cathode materials:
[0147] The same method as in Example 1 was used except that the Mg content of 0.020 and the Zn content of 0.020 were adjusted to 0.040. The volume average particle size D of the obtained layered oxide positive electrode material was v 50 is 8.5 microns.
[0148] Comparative Example 5
[0149] The general formula for preparation is Na 1.070 Cu 0.08 Ni 0.45 Mn 0.55 Ti 0.14 Ca 0.005 O 2.450 Layered oxide cathode materials:
[0150] The same as Example 1 except that Mg and Zn were not added and the other parameters were adjusted according to the general formula. v 50 is 8.5 microns.
[0151] Comparative Example 6
[0152] The general formula for preparation is Na 1.180 Cu 0.02 Ni 0.50 Mn 0.50 Ti 0.08 Zn 0.030 Mg 0.030 Sr 0.005 Ba 0.005 O 2.340 Layered oxide cathode materials:
[0153] The other aspects are the same as those of Example 2 except that the content of Cu is adjusted from 0.03 to 0.02, and the other aspects are adjusted according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 7.5 microns.
[0154] Comparative Example 7
[0155] The general formula for preparation is Na 1.200 Cu 0.03 Ni 0.50 Mn 0.50 Ti 0.07 Zn 0.030 Mg 0.030Sr 0.005 Ba 0.005 O 2.340 Layered oxide cathode materials:
[0156] The same as Example 2 except for the following: the content of Ti was adjusted from 0.08 to 0.07, and the other adjustments were made according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 7.5 microns.
[0157] Comparative Example 8
[0158] The general formula for preparation is Na 1.220 Cu 0.03 Ni 0.51 Mn 0.49 Ti 0.08 Zn 0.030 Mg 0.030 Sr 0.005 Ba 0.005 O 2.360 Layered oxide cathode materials:
[0159] The other aspects are the same as those of Example 2 except that the Ni content is adjusted from 0.50 to 0.51, and the other aspects are adjusted according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 7.5 microns.
[0160] Comparative Example 9
[0161] The general formula for preparation is Na 1.224 Cu 0.03 Ni 0.51 Mn 0.49 Ti 0.08 Zn 0.030 Mg 0.030 Sr 0.006 Ba 0.006 O 2.364 Layered oxide cathode materials:
[0162] The same as Example 2 except for the following: the content of Ni was adjusted from 0.50 to 0.51, the content of Sr and Ba were adjusted from 0.005 to 0.006 respectively, and the other adjustments were made according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 7.5 microns.
[0163] Comparative Example 10
[0164] The general formula for preparation is Na 1.220 Cu 0.03 Ni 0.50 Mn 0.50 Ti 0.08 Zn0.035 Mg 0.035 Sr 0.005 Ba 0.005 O 2.380 Layered oxide cathode materials:
[0165] The same as Example 2 except for the following: Zn and Mg were adjusted from 0.030 to 0.035 respectively, so that the final total amount s of the added divalent elements Cu and H was adjusted from 0.100 to 0.110, and the other adjustments were made according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 7.5 microns.
[0166] Comparative Example 11
[0167] The general formula for preparation is Na 1.142 Cu 0.12 Ni 0.40 Mn 0.60 Ti 0.16 Zn 0.030 Mg 0.020 Sr 0.001 O 2.662 Layered oxide cathode materials:
[0168] The other aspects are the same as those of Example 3 except that the content of Cu is adjusted from 0.11 to 0.12, and the other aspects are adjusted according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 9.5 microns.
[0169] Comparative Example 12
[0170] The general formula for preparation is Na 1.122 Cu 0.11 Ni 0.40 Mn 0.60 Ti 0.17 Zn 0.030 Mg 0.020 Sr 0.001 O 2.662 Layered oxide cathode materials:
[0171] The same as Example 3 except for the following: the Ti content was adjusted from 0.16 to 0.17, and the other adjustments were made according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 9.5 microns.
[0172] Comparative Example 13
[0173] The general formula for preparation is Na 1.102 Cu 0.11 Ni 0.39 Mn 0.61 Ti0.16 Zn 0.030 Mg 0.020 Sr 0.001 O 2.642 Layered oxide cathode materials:
[0174] The other aspects are the same as those of Example 3 except that the Ni content is adjusted from 0.40 to 0.39, and the other aspects are adjusted according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 9.5 microns.
[0175] Comparative Example 14
[0176] The general formula for preparation is Na 1.120 Cu 0.11 Ni 0.40 Mn 0.60 Ti 0.16 Zn 0.030 Mg 0.020 O 2.640 Layered oxide cathode materials:
[0177] The same as Example 3 except that Sr was not added and other parameters were adjusted according to the general formula. The volume average particle size D of the obtained layered oxide positive electrode material v 50 is 9.5 microns.
[0178] Comparative Example 15
[0179] The general formula for preparation is Na 1.260 Cu 0.08 Ni 0.49 Fe 0.02 Mn 0.49 Ti 0.12 Zn 0.020 Mg 0.020 Ca 0.006 Sr 0.002 Ba 0.00 2O 2.500 Layered oxide cathode materials:
[0180] The same as Example 6 except for the following: iron oxide was added so that the content of Fe in the general formula was 0.02, and the other adjustments were made according to the general formula. v 50 is 10.7 microns.
[0181] 2. Evaluation Example
[0182] 1. pH test
[0183] According to the mass ratio of layered oxide positive electrode material: distilled water = 1:20, take an appropriate amount of positive electrode material and add it to the corresponding amount of distilled water, and then stir it magnetically at room temperature at a speed of 600±20r / min for 10 minutes to mix evenly. Then, after the resulting mixture is allowed to stand for 5 minutes, the pH of the mixture is measured at a constant temperature of 25°C by a pH meter (METTLER TOLEDO pH meter FE22-Standard), which is the pH of the corresponding material. The pH test results are shown in Table 1.
[0184] 2. Moisture test
[0185] The test was performed using a Karl Fischer moisture tester (model Compact V10S). The moisture test results are shown in Table 1.
[0186] 3. Residual alkali test
[0187] The residual alkali (sodium carbonate, sodium hydroxide) of the sample was tested using an automatic potentiometric titrator (model: METTLER TOLEDO G20) and converted into Na% content (based on the total weight of the Fe-free layered oxide positive electrode material). The residual alkali test results are shown in Table 1.
[0188] 4.D v 50 Particle size test
[0189] Use Malvern 3000 laser particle size analyzer for testing. Select lithium cobalt oxide as the standard substance and water as the dispersant, and set the following instrument test parameters: test time 10s, test number 3, shading 6-15%, stirring speed 2800r / min, ultrasonic mode on, power 50%. Click the laser particle size analyzer (Malvern 3000 laser particle size analyzer) to start the test, and then add the primary sintering product or positive electrode material to the sample pool, control the amount added to adjust the shading of the sample pool to 6-15%. The instrument automatically repeats the test 3 times, and the average value of the 3 tests is taken as the mean of the test results.
[0190] 5. SEM test
[0191] Hitachi Regulus8100 was used for testing, with an acceleration voltage of 5.0kV, a magnification of 10k, and general morphology photography.
[0192] Figure 10-12 They are SEM images of layered oxide positive electrode materials prepared according to Comparative Example 5, Example 2 and Example 3 of the present invention, respectively. Fig.11 This is a SEM picture of the layered oxide positive electrode material according to Example 2 of the present invention, which exhibits an agglomerated single crystal-like morphology; Fig.12 : is a SEM picture of the layered oxide positive electrode material according to Example 3 of the present invention, which exhibits a slightly adhered single crystal morphology.
[0193] 6.SEM-EDS test
[0194] SEM-EDS tests were performed using a Hitachi Regulus8100 with an accelerating voltage of 5.0 kV and a magnification of 10k.
[0195] Fig. 9 This is the SEM-EDS test result according to Example 1 of the present invention. Fig. 9 It can be seen that in the layered oxide positive electrode material according to Example 1 of the present invention, the Ca element is evenly distributed on the surface of the material.
[0196] Combination Fig. 9 and Fig.10 It can be found that the primary crystal grains of the layered oxide positive electrode material of Example 1 are fine, while the layered oxide positive electrode material of Comparative Example 5 is in the form of flakes or blocks.
[0197] 7.XRD test
[0198] The test was carried out using an X-ray diffractometer (model Bruker D8 ADVANCE) with a copper target (Cu-Kα) (accelerating voltage 40 KV, current 40 mA) (λ=1.54056 nm), a range of 10-80 degrees, a step size of 0.02 degrees, a time of 0.2, and a total duration of 712 seconds.
[0199] Figure 8 The XRD spectrum of the layered oxide positive electrode material according to Example 1 of the present invention and the standard XRD spectrum PDF#54-0887(O3) are shown. Figure 8 It can be judged that the layered oxide positive electrode material prepared according to Example 1 of the present invention is a pure O3 phase layered oxide positive electrode material.
[0200] 8.DSC test
[0201] The test was conducted using a NETZSCH 300-classic differential scanning calorimeter. The fully charged button cell was disassembled in a glove box with an argon atmosphere (the fully charged positive electrode was in a de-sodium state, at which time the material structure stability was poor, and this state is a common test method for testing the safety performance of the material). 20 mg of the positive electrode containing the electrolyte was taken out and tested directly. The test atmosphere was argon, and the temperature was increased from 100°C to 380°C at a rate of 5°C / min.
[0202] Fig.13The DSC test results of the layered oxide positive electrode material of Comparative Example 15 and Example 6 of the present invention are shown. The DSC data show that Comparative Example 15 has obvious exothermic peaks near 262°C and 303.4°C. In contrast, the layered oxide positive electrode material of Example 6 of the present invention without Fe element has only one exothermic peak at 310.8°C. The number of exothermic peaks of Example 6 is reduced, and the exothermic temperature is delayed, indicating that it can withstand higher temperatures and has better safety performance.
[0203] 9. Electrochemical performance test
[0204] The positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-15, SP (Swiss Special High Conductive Carbon Black SUPER P) and polyvinylidene fluoride (PVDF, PVDF5130 purchased from SOLVAY) glue (mass fraction 10%, solvent N-methylpyrrolidone (NMP)) were mixed in a mass ratio of 90:5:5, and NMP was added to make a viscous glue. The prepared glue was coated on aluminum foil (thickness 16μm), and then baked in a vacuum drying oven at 120℃ for 12 hours to obtain a positive electrode sheet (active material mass 5mg / cm 2 ). A metal sodium sheet (Aladdin) was used as the counter electrode (thickness 300±50μm). A glass fiber (Waterman) was used as the diaphragm (thickness 675μm). A NaPF6 solution with a sodium ion concentration of 1 mol / L was prepared. The solvent was a mixture of EC:DMC (volume ratio) = 1:1. A 2032 button cell was assembled in an Ar protection glove box.
[0205] 9.1 Initial Discharge Specific Capacity (Gram Capacity) and Rate Performance
[0206] After the 2032 button cell is assembled, place the button cell at 25°C, charge it to 4.3V at 0.1C constant current, and then let it stand for 5 minutes; then discharge it to 2.0V at 0.1C constant current, and record the discharge capacity. Test the other two assembled 2032 button cells according to the above method. Calculate the average of the discharge capacity of the three tests, which is the initial discharge capacity test result at 0.1C rate (unit: mAh / g). Plot the voltage (V) of the first charge and discharge test at 0.1C rate against the specific capacity (mAh / g) to obtain the first charge and discharge curve.
[0207] Keeping other conditions unchanged, change the charge and discharge rate to 0.5C, and obtain the initial discharge capacity test result (unit: mAh / g) at 0.5C rate. Divide the initial discharge capacity at 0.5C rate by the initial discharge capacity at 0.1C rate, which is the rate value of 0.5C / 0.1C.
[0208] Figure 1-7 The first charge and discharge curves of button cells prepared using the layered oxide positive electrode materials of Examples 1-6 and Comparative Example 5 of the present invention are shown respectively. Figure 1-6 The charge and discharge curves are relatively smooth and rounded, indicating that the material has fewer phase changes and a relatively stable structure. Figure 7 This is the first week charge and discharge curve of comparative example 5. Compared with example 1, the curve and capacity of the charging process do not change much, mainly because the capacity of the discharge part decreases significantly.
[0209] 9.2 Cycle retention rate
[0210] At 25°C, charge the battery to 4.3V at 0.5C constant current, then let it stand for 5 minutes, then discharge it to 2.0V at 0.5C constant current, then let it stand for 5 minutes. This is a charge and discharge cycle, and the discharge capacity is recorded as the discharge capacity of the first cycle of the battery. Perform 100 cycles of charge and discharge tests on the battery according to the above method, and record the discharge capacity of the 100th cycle. Then calculate the discharge capacity of the 100th cycle / discharge capacity of the first cycle × 100%. Test the other two assembled 2032 button batteries according to the above method. Take the average of the results of the three tests to get the cycle retention rate when the cycle is 100 times at a rate of 0.5C.
[0211] The electrochemical properties of the sodium ion secondary batteries prepared from the layered oxide positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-15, as well as the test results of pH, moisture and residual alkali are summarized in Table 1.
[0212] Table 1: Electrochemical performance of Examples 1-6 and Comparative Examples 1-15
[0213]
[0214]
[0215] From Table 1 and in combination with the attached Figure 1-13 It can be seen that the Fe-free layered oxide positive electrode materials of Examples 1-6 of the present invention have better comprehensive performance in initial discharge specific capacity, rate performance, cycle performance and safety performance than those of Comparative Examples 1-15.
[0216] Referring to Example 1 and Comparative Examples 1-5, the main difference between Example 1 and Comparative Examples 1-5 is that the Zn content and the Mg content are different. Specifically, the Zn content and the Mg content of Example 1 are 0.020 and 0.020, respectively, while the Zn content and the Mg content of Comparative Example 1 are 0.018 and 0.020, respectively, the Zn content and the Mg content of Comparative Example 2 are 0.020 and 0.018, respectively, the Zn content and the Mg content of Comparative Example 3 are 0.040 and 0, respectively, the Zn content and the Mg content of Comparative Example 4 are 0 and 0.040, respectively, and Comparative Example 5 does not include Zn and Mg. The comprehensive electrochemical performance of Example 1 (initial discharge specific capacity 175.6 mAh / g, rate 0.96, cycle retention rate 0.93, the same order below) is better than that of Comparative Example 1 (173.3 mAh / g, 0.93, 0.88), Comparative Example 2 (172.7 mAh / g, 0.92, 0.90), Comparative Example 3 (175.3 mAh / g, 0.90, 0.89), Comparative Example 4 (172.6 mAh / g, 0.90, 0.87), and Comparative Example 5 (160.1 mAh / g, 0.88, 0.92).
[0217] Referring to Examples 2-3, and Comparative Examples 6 and 11, the main difference between Examples 2-3 and Comparative Examples 6 and 11 is that the Cu content is different. Specifically, the Cu content of Example 2 is 0.03, the Cu content of Example 3 is 0.11, and the Cu contents of Comparative Examples 6 and 11 are 0.02 and 0.12, respectively. The comprehensive electrochemical performance of Example 2 (187.8 mAh / g, 0.92, 0.90) and Example 3 (168.3 mAh / g, 0.97, 0.95) is better than that of Comparative Example 6 (185.8 mAh / g, 0.91, 0.87) and Comparative Example 11 (169.2 mAh / g, 0.91, 0.83), respectively.
[0218] Referring to Examples 2-3, and Comparative Examples 8 and 13, the main difference between Examples 2-3 and Comparative Examples 8 and 13 is that the Ni (or Mn) content is different. Specifically, the Ni content of Example 2 is 0.50, the Ni content of Example 3 is 0.40, and the Ni content of Comparative Examples 8 and 13 is 0.51 and 0.49, respectively. The comprehensive electrochemical performance of Example 2 (187.8 mAh / g, 0.92, 0.90) and Example 3 (168.3 mAh / g, 0.97, 0.95) is better than that of Comparative Example 8 (185.6 mAh / g, 0.88, 0.86) and Comparative Example 13 (160.2 mAh / g, 0.94, 0.91), respectively.
[0219] Referring to Examples 2-3, and Comparative Examples 7 and 12, the main difference between Examples 2-3 and Comparative Examples 7 and 12 is the different Ti contents. Specifically, the Ti content of Example 2 is 0.08, the Ti content of Example 3 is 0.16, and the Ti contents of Comparative Examples 7 and 12 are 0.07 and 0.17, respectively. The comprehensive electrochemical performance of Example 2 (187.8 mAh / g, 0.92, 0.90) and Example 3 (168.3 mAh / g, 0.97, 0.95) is better than that of Comparative Example 7 (187.9 mAh / g, 0.88, 0.86) and Comparative Example 12 (164.3 mAh / g, 0.95, 0.92), respectively.
[0220] In addition, the inventors have also found that when the content x of the +2-valent metal element Cu, the content sx of the doping elements such as Zn, Mg, Ca, Sr, Ba, and the content j of the +4-valent metal element Ti in the general formula of the layered oxide positive electrode material satisfy x+0.04<s≤j+0.02, it is beneficial to obtain an increased initial discharge specific capacity and improved rate performance and cycle performance, especially improved rate performance and cycle performance (see, for example, Example 2 and Comparative Example 10).
[0221] In addition, comparing Example 6 and Comparative Example 15 and combining Fig.13 It can be found that for the positive electrode material system of the present invention, the layered oxide positive electrode material without Fe element has fewer peaks in the DSC test and the peak positions are further back, indicating that the heat resistance is better than that containing Fe element and the safety performance is better.
[0222] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.
Claims
1. A layered oxide positive electrode material without Fe element, which has the following general formula: So 2y+2s Cu x Ni y Mr 1-y Tea j A s-x O 2+2s+2j in, 0.03≤x≤0.11, preferably 0.03≤x≤0.08; 0.40≤y≤0.50, preferably 0.45≤y≤0.50, more preferably 0.47≤y≤0.50; 0.08≤j≤0.16, preferably 0.08≤j≤0.14, for example 0.08≤j≤0.12 or 0.12≤j≤0.14; x+0.04<s≤j+0.02; H is a +2 valent active metal element, H includes the subscript Zn content is above 0.020, preferably in the range of 0.020 to 0.040, more preferably in the range of 0.020 to 0.030, and Mg content is above 0.020, preferably in the range of 0.020 to 0.050, more preferably in the range of 0.020 to 0.030, and further comprises one or more of Ca, Sr and Ba, wherein each of Ca, Sr and Ba, when present, has a subscript of ≤0.010; the general formula satisfies valence balance. 2 . The Fe-free layered oxide positive electrode material according to claim 1 , wherein s is in the range of 0.10 to 0.18, preferably 0.10 to 0.
13.
3. The Fe-free layered oxide positive electrode material according to claim 1 or 2, wherein the sum of the subscripts of Ca, Sr and Ba is 0.001 to 0.
010.
4. The Fe-free layered oxide positive electrode material according to any one of claims 1 to 3, wherein H is one selected from Zn+Mg+Ca, Zn+Mg+Sr, Zn+Mg+Ba, Zn+Mg+Ca+Sr, Zn+Mg+Ca+Ba, Zn+Mg+Sr+Ba, and Zn+Mg+Ca+Sr+Ba.
5. The Fe-free layered oxide positive electrode material according to any one of claims 1 to 4, wherein the molar ratio of Cu to Ni is in the range of 0.06 to 0.28, preferably 0.06 to 0.18, for example 0.06 to 0.
16.
6. The Fe-free layered oxide positive electrode material according to any one of claims 1 to 5, wherein the Fe-free positive electrode material is an O3 phase positive electrode material.
7. A method for preparing the Fe-free layered oxide positive electrode material according to any one of claims 1 to 6, comprising the following steps: Step a: uniformly mixing a Na source, a Cu source, a Ti source, a Ni source, a Mn source, and a H source in a stoichiometric ratio, wherein the H source comprises a Zn source, a Mg source, and further comprises one or more of a Ca source, a Sr source, and a Ba source; and Step b: sintering the mixture obtained in step a at 800 to 1000° C. for 10 to 30 hours, cooling, and optionally crushing and sieving.
8. The method according to claim 7, wherein the Na source is one or more selected from the following compounds: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide and sodium oxide; The Cu source is one or more selected from the following compounds: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide, copper oxide and cuprous oxide; The Ti source is one or more selected from the following compounds: titanium carbonate, titanium nitrate, titanium acetate, titanium oxalate, titanium hydroxide and titanium oxide; The Ni source is one or more selected from the following compounds: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel manganese hydroxide and nickel oxide; The Mn source is one or more selected from the following compounds: manganese carbonate, manganese nitrate, manganese acetate, manganese oxalate, manganese hydroxide, nickel manganese hydroxide and manganese oxide; The Zn source is one or more compounds selected from the following: zinc carbonate, zinc nitrate, zinc acetate, zinc oxalate, zinc hydroxide and zinc oxide; The Mg source is one or more selected from the following compounds: magnesium carbonate, magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide and magnesium oxide; The Ca source is one or more compounds selected from the following: calcium carbonate, calcium nitrate, calcium acetate, calcium oxalate, calcium hydroxide and calcium oxide; The Sr source is one or more selected from the following compounds: strontium carbonate, strontium nitrate, strontium acetate, strontium oxalate, strontium hydroxide and strontium oxide; and The Ba source is one or more selected from the following compounds: barium carbonate, barium nitrate, barium acetate, barium oxalate, barium hydroxide and barium oxide. 9 . A positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the Fe-free layered oxide positive electrode material according to claim 1 . 10 . A sodium ion secondary battery comprising the positive electrode composition according to claim 9 .
11. Use of the sodium ion secondary battery according to claim 10 in energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
